General Lorentz invariant representation of the NN interaction applied to quasielastic scattering of polarized protons - Van der Ventel, B. I. S. (Brandon Izak Samuel) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 1999.